Osteology and phylogenetic relationships of Tyrannotitan chubutensis Novas, de Valais, VickersRich and Rich, 2005 (Theropoda: Carcharodontosauridae) from the Lower Cretaceous of Patagonia, Argentina - Canale, Juan Ignacio (2013)
The theropod clade Carcharodontosauridae is a broadly distributed group of large allosauroid theropods. The carcharodontosaurids recorded in the Albian – Cenomanian of Gondwana are the youngest and most derived members of this clade. Tyrannotitan chubutensis, from the Cerro Castan˜o Member of Cerro Barcino Formation (Albian; Chubut Group), Central Patagonia, Argentina, is of prime interest among Gondwanan carcharodontosaurids as it represents the oldest record of the group. Here we offer a detailed osteological comparative description of the holotype and paratype of Tyrannotitan chubutensis together with a new diagnosis of the species. The new information results in a better understanding of this taxon and Carcharodontosauridae. Furthermore, a comparative study of the anatomy of the pectoral girdle of Giganotosaurus is reinterpreted as very similar to that of Tyrannotitan and Mapusaurus. We also present a phylogenetic analysis of Carcharodontosauridae that recovers Tyrannotitan as a derived carcharodontosaurid, being the sister group of the clade formed by Giganotosaurus and Mapusaurus, all nested in the clade Giganotosaurini.